2001
DOI: 10.1038/87730
|View full text |Cite
|
Sign up to set email alerts
|

Naïve CTLs require a single brief period of antigenic stimulation for clonal expansion and differentiation

Abstract: In defense of the host, the immune system must often raise an effective cytotoxic T lymphocyte (CTL) response from a small number of clonal precursors. The degree to which activation stimuli regulate the expansion and differentiation of naïve CTLs, however, remains unknown. Using an engineered antigen-presenting cell (APC) system that allows control over antigenic stimulation, we studied the signaling duration requirements for priming and clonal expansion of naïve CTLs. We found that naïve CTLs become committe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
622
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 788 publications
(681 citation statements)
references
References 45 publications
54
622
5
Order By: Relevance
“…Interestingly, late clearance did not hinder the activation of the donor T cells [76]. This corroborates with several reports that demonstrate antigenic stimulation, before APC clearance, is all that is required to initiate activation and proliferation of T cells [80,81].…”
Section: Effects Of Lymphodepleting Radiation and Chemotherapy On Apcsupporting
confidence: 90%
“…Interestingly, late clearance did not hinder the activation of the donor T cells [76]. This corroborates with several reports that demonstrate antigenic stimulation, before APC clearance, is all that is required to initiate activation and proliferation of T cells [80,81].…”
Section: Effects Of Lymphodepleting Radiation and Chemotherapy On Apcsupporting
confidence: 90%
“…Earlier studies reported similar synchrony within the CD8 + T cell compartment, among CTL specific for different epitopes from the same pathogen [2,21]. Further analysis of this synchrony within T cell responses revealed that the in vivo kinetics of expansion and contraction are determined very early during the initial phase of the immune response and are remarkably independent of later environmental factors and changes, such as the in vivo halflife of a particular antigen or the duration of infection [2,22,[24][25][26]. The results of our comparative study indicate that the initial activation and 'programming' of epitopespecific CD4 + and CD8 + T cells occur within a similar time frame during infection.…”
Section: Discussionmentioning
confidence: 74%
“…Whether this difference was due to in vivo versus in vitro stimulation or the nature of the stimulus was not clear. Within the first 20 h of stimulation, T cells receive the signals they need to undergo a pre-programmed expansion phase that appears to be independent of further T cell activation [33][34][35][36][37]. Recent evidence also suggests that CD8 T cells kill antigen-presenting DC during the first few days of the response [38].…”
Section: Introductionmentioning
confidence: 99%